THE SPEECH ACTS AND CONVERSATIONAL IMPLICATURE OF WISE'S THE SOUND OF MUSIC - Chusni Hadiati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2009)
The conversation's implicatures as the impact of the violation of the cooperative principle's maxims of Grice (1975) can be classified into the speech act category of Searle (1975). The movie "The Sound of Music" is a masterpiece of Robert Wise winning many international awards. The conversations in it have some interesting characteristics worthy to investigate. The implicatures of the maxim violation in the movie's dialogue can be categorized into: (1) representative: protecting, refusing, pretending, and stating a joke (2) directive: flirting, asking other to go, keeping a secret (3) commissives: accepting an offer, (4) expressive: mocking, entertaining, calming down, and pleasing.